PENGARUH BYSTANDER EFFECT, KETAATAN ATURAN AKUNTANSI DAN RELIGIUSITAS TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Ni Wayan Tutik Aprianti; Ni Putu Ayu Kusumawati; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2022)
Fraud has a negative result on the survival of the organization. cheating must be solved quickly. This paper is made to provide a solution to the existence of fraud in institutions. diaman will look at factors related to fraud such as the Bystander Effect, Compliance with Accounting Rules and Religiosity. This research was conducted at the LPD in Abyansemal District with a sample of 99 respondents. The results reveal that fraud tends to increase when there is a high Bystander Effect in the organization. On the other hand, accounting fraud can be avoided through the obedient attitude of employees to accounting rules and the high attitude of religiosity of the individual.